Making money, making music : history and core concepts - Bruenger, David, 1953- (University of California Press, 2016)
"Making money, making music is an alternative music business text, providing an entrepreneurial toolbox, based on historical analysis, trends, and patterns in music enterprise. It begins by introducing core principles and processes and shows how to apply them adaptively to new contexts, so that students gain a deeper understanding not only of how things work in the music business, but why. By applying essential concepts to a variety of real-life situations, students improve their capacity to critically analyze, solve problems, and even predict where music and money will converge in a rapidly evolving culture and marketplace."--Provided by publisher